(untitled) (Aporte Santiaguino, 2019)
The Shullcas River is born in the Chuspicocha and Lazo Untay lagoons located on the western ank of the Huaytapallana, it is the main source of water for human consumption in the city of Huancayo. The objective of the research work is to apply the Box - Jenkins, and Holt - Winters models for the forecast of the monthly ows of the Shullcas river in the Chamisería station. The Holt -Winters multiplicative model is not applicable because the predicted monthly ows have a secular tendency The ARIMA model (1,0, 0)(2, 1, 1)12 is the most suitable for the forecast of monthly ows because they have the lowest value of the Akaike information criterion (0, 551)